Age‐specific influence of wheezing phenotypes on pre‐adolescent and adolescent health‐related quality of life. Issue 8 (13th October 2014) - Braig, Stefanie; Brandt, Stephanie; Wabitsch, Martin; Florath, Ines; Brenner, Hermann; Rothenbacher, Dietrich; Genuneit, Jon
Abstract Introduction Asthma is associated with diminished health‐related quality of life (HRQoL). Particularly in adolescence, asthma may be under‐diagnosed and undertreated or poorly managed. Therefore, we aimed to determine the association between childhood wheezing phenotypes rather than asthma and adolescent HRQoL in children aged 10–17 yr. Methods We analyzed the data from two prospective population‐based cohort studies (n = 604 and n = 1804) conducted in southern Germany with baseline assessments in 2000 and 2006 and follow‐ups at frequent intervals. Parent‐reported wheeze was categorized into never, early transient, persistent, and late‐onset wheeze. We assessed child‐reported HRQoL in seven scales using the validated KINDL‐R. Multivariate linear regression models were computed. Results Participants with late‐onset wheeze had significantly lower values in all HRQoL scales, but physical well‐being compared to never wheezers. Early transient wheeze was negatively associated with three HRQoL scales only (family, school, and total). These effects were confined to the oldest age group (≥13.5 yr) in one study. Persistent wheeze was not associated with HRQoL. Conclusions In teenagers, late‐onset wheezers seem to be particularly vulnerable for impairments in psychosocial aspects of health‐related quality of life. They may therefore require particular attention with regard to education about asthma management and potentially family‐based psychosocial intervention.